Critique of everyday life - Lefebvre, Henri, 1901-1991. (London ; New York : Verso, 1991)
'...Written at the birth of post-war consumerism, the Critique was a philosophical inspiration for the 1968 student revolution in France and is considered to be the founding text of all that we now know as cultural studies, as well as a major influence on the fields of contemporary philosophy, geography, sociology, architecture, political theory and urbanism. A work of enormous range and subtlety, Lefebvre takes as his starting-point and guide the "trivial" details of quotidian experience: an experience colonized by the commodity, shadowed by inauthenticity, yet one which remains the only source of resistance and change. This is an enduringly radical text, untimely today only in its intransigense and optimism"--publisher
v. 1. Introduction -- v. 2. Foundations for a sociology of the everyday -- v. 3. From modernity to modernism (towards a metaphilosophy of daily life).
Translation of the 2nd ed. of: Critique de la vie quotidienne.
Vol. 1 includes bibliographical references (p. 255-273) and index; vol. 2 includes bibliographical references and index (p. 371-380); vol. 3 includes index (p. 173-179).
Keywords: Life; Philosophy, Marxist; Sociology -- Sociology